Prevalência de disfunções orofaciais em pacientes com diagnóstico de Leucemia Aguda no Hemocento do Amazonas - Sousa Filho, Grijalba Rodrigues de (2021)
Infant-juvenile patients with acute leukemia may present systemic weakness, pain and discomfort during chewing and swallowing, compromising orofacial functions, including swallowing. Objective: To identify the occurrence of orofacial disorders in juvenile patients diagnosed with acute leukemia undergoing remission chemotherapy, treated at FHEMOAM. Method: Over a period of 16 months, 40 patients with acute leukemia, aged between 3 and 18 years, were admitted to the Hospital Foundation of Hematology and Hemotherapy of Amazonas - HEMOAM for a cross-sectional study. Of these, 23 were included in the research and initially submitted to dental evaluation, and the to the assessment of orofacial functions and acoustic analysis of swallowing, using the Nordic Orofacial Test-Screening (NOT-S) and Acoustic Assessment Protocol (PAAD) for liquid, pasty and solid, between the D30 and D33 of the remission induction phase. Results: Orofacial dysfunction was observed in 47.8% (n=11) of the cases, 100% (n=11) of them with alterations in domain VI (Dryness of the Mouth) and 81.8% (n=9) in domain IV (Chewing and Swallowing) of NOT-S. In the acoustic evaluation of swallowing, not all patients could be analyzed. The medians of Frequency, Intensity and Time in the 3 consistencies were, respectively, Liquid (n = 23/23): 920Hz, 76.1dB and 0.9s; Puree (n = 22/23): 846 Hz, 85dB and 1.1s; Solid (n = 17/23): 689 Hz, 54.9 dB and 0.9s. The frequency and intensity medians for solids were below the expected for the PAAD normality standard. Conclusion: The occurrence of orofacial dysfunction in the induction phase is frequent and needs to be better studied. Future studies on these dysfunctions are needed to better understand the impacts and support therapeutic strategies